Salmonella Populations inside Host Cells - Castanheira, Sónia; García-del Portillo, Francisco (Frontiers in Cellular and Infection Microbiology, 2017)
Bacteria of the Salmonella genus cause diseases ranging from gastroenteritis to life-threatening typhoid fever and are among the most successful intracellular pathogens known. After the invasion of the eukaryotic cell, Salmonella exhibits contrasting lifestyles with different replication rates and subcellular locations. Although Salmonella hyper-replicates in the cytosol of certain host cell types, most invading bacteria remain within vacuoles in which the pathogen proliferates at moderate rates or persists in a dormant-like state. Remarkably, these cytosolic and intra-vacuolar intracellular lifestyles are not mutually exclusive and can co-exist in the same infected host cell. The mechanisms that direct the invading bacterium to follow the cytosolic or intra-vacuolar “pathway” remain poorly understood. In vitro studies show predominance of either the cytosolic or the intra-vacuolar population depending on the host cell type invaded by the pathogen. The host and pathogen factors controlling phagosomal membrane integrity and, as consequence, the egress into the cytosol, are intensively investigated. Other aspects of major interest are the host defenses that may affect differentially the cytosolic and intra-vacuolar populations and the strategies used by the pathogen to circumvent these attacks. Here, we summarize current knowledge about these Salmonella intracellular subpopulations and discuss how they emerge during the interaction of this pathogen with the eukaryotic cell.